Пристрій для завантаження сипких матеріалів в клапанні мішки - Оришака, О. В.; Кравцов, А. О.; Оришака, В. О.; Артюхов, А. М.; Oryshaka, O.; Kravtsov, A.; Oryshaka, V.; Artiukhov, A.; Оришака, О. В.; Кравцов, А. А.; Оришака, В. А.; Артюхов, А. Н. (Український інститут промислової власності, 2008)
Корисна модель відноситься до фасувально-пакувального обладнання і може бути використаний в агропромисловості, будівельній, хімічній галузях господарства, а також на підприємствах, які здійснюють фасування сипких матеріалів. A device for loading of bulk materials into the valve bags, in which the inlet part of the receiving cells overlaps the outlet of product line, and on the outlet part of receiving cells unloading pipes are installed with possibility to perform swinging movement in such a way that in the end positions the directions of the channels of unloading pipes coincide with one of the channels of corresponding loaders, which are made in the form of a tee, which includes an inlet channel and a branching, in this case the swinging movement of unloading pipes is performed around outlet parts of receiving cells.
Device for loading of bulk materials into valve bags